Peningkatan Kualitas Penanganan Pascapanen Kopi Di Gapoktan Sejahtera Umbulharjo Cangkringan Sleman Yogyakarta - Yuliana Reni Swasti; Dinar Gumilang Jati; Ekawati Purwijantiningsih (Institut Pertanian Bogor, 2022)
The coffee farmers of Farmer Union (Gapoktan) Sejahtera Umbulharjo had a lack of knowledge of good coffee post-harvest handling such as the best harvesting time, fermentation, drying, roasting green been extracting, and packaging roasted coffee need to be improved through extension and training postharvest handing. This research aimed to improve the quality of the coffee postharvest handling. The methods employed are extension and training. The result showed the increase of Gapoktan farmers’ understanding, especially in harvesting technique (pre-test score 33,33 and post-test score 93,33) and drying coffee (pre-test score 44,44 and post-test score 100). In addition, the improvement of postharvest handling reduced the drying time from 30 days to 14 days.